2013
DOI: 10.20896/saci.v5i2.278
|View full text |Cite
|
Sign up to set email alerts
|

Desert Dwellers’ Meaning and Existence of Spirituality: A Gendered Case Study of Cholistan, Pakistan

Abstract: Cholistan is the second largest desert of Pakistan, which is locally known as Rohi (Mughal, 1994). This paper is an ethnographic endeavour that sketches living in the desert and is about the traditional way in which people handle desolateness and powerlessness in that severely parched earth. Men and women seem to appear primordially linked to and in agreement with their environment. Their contentment is heartfelt, an aspect that seems to emerge from their belief that there is a spiritual solution for every pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…There are, however emerging social work research in Pakistan applying for both borrowed and local scholarship. For instance, in 2017 Aisha Shoukat and Venkat Rao Pulla, in their article titled Desert Dwellers' Meaning and Existence of Spirituality: A Gendered Case Study of Cholistan, Pakistan demonstrated how the desert dwellers of Cholistan use spirituality as a form of resilience to lead an eco-friendly life (Shoukat & Pulla, 2017).…”
Section: Islamic Republic Of Pakistanmentioning
confidence: 99%
“…There are, however emerging social work research in Pakistan applying for both borrowed and local scholarship. For instance, in 2017 Aisha Shoukat and Venkat Rao Pulla, in their article titled Desert Dwellers' Meaning and Existence of Spirituality: A Gendered Case Study of Cholistan, Pakistan demonstrated how the desert dwellers of Cholistan use spirituality as a form of resilience to lead an eco-friendly life (Shoukat & Pulla, 2017).…”
Section: Islamic Republic Of Pakistanmentioning
confidence: 99%